Transforming AI-generated text-to-image concepts into functional final designs: a case study on lighting product design in industrial design education / Mohd Hamidi Adha Mohd Amin - Mohd Amin, Mohd Hamidi Adha (Penerbit UiTM (UiTM Press), 2025)
This study explores the integration of generative AI, particularly textto-image generators, into industrial design education and its role in enhancing creativity during the idea-generation process. Focusing on a lighting product design project, the research examines how students use AI-generated concepts as a starting point and refine them through sketches and 3D models into fully functional designs. Generative AI has significant potential to facilitate creativity by breaking down traditional barriers to ideation and speeding up the concept-generation process. However, turning creative output into practical, manufacturable products can be challenging. The research involved 20 Bachelor of Industrial Design students tasked with transforming AI-generated imagery into functional lighting products. The methodology followed a threephase process: AI-based concept generation, design refinement through sketches, and final 3D modeling. The findings reveal that while AI tools provide creative inspiration, students need to make substantial refinements to ensure the designs are both practical and user-centered. Main adjustments included form simplification, functional enhancements, and material considerations. This highlights the critical role of human intervention in bridging the gap between AI-generated concepts and fully realized, functional products. This research contributes to the growing understanding of how to incorporate generative AI into industrial design education effectively.